Traumatic Craniocervical Dissociation in Patients with Congenital Assimilation of the Atlas to the Occiput - Celeste Tavolaro; Hector Pulido; Richard Bransford; Carlo Bellabarba (Case Reports in Orthopedics, 2019)
Traumatic atlantooccipital dissociation (AOD) is a severe and usually fatal injury. Patients with assimilation of the atlas to the skull are exposed to a higher risk of injury and delay diagnosis due to the abnormal anatomy. We report two cases of acute traumatic craniocervical dislocation in patients with baseline congenital assimilation of the atlas to the skull. Computer tomography (CT) was used to identify the injury. Computer tomography angiography (CTA) showed variations of the vertebral arteries’ location on both patients. Assimilation of the atlas was complete in patient one and partial in patient two. Emergent surgical instrumentation and fusion were performed with a very careful and meticulous posterior dissection. As general rule, most of the patients with CCD will undergo occiput to C2 posterior segmental instrumentation and fusion. In the presented cases, a more extensive fusion was necessary based on the type and severity of the CCJ injury and the anatomical anomalies associated. Postoperatively, patient one remained neurologically intact and patient two died. Alternative fixation techniques should be used to minimize risk of VA injury during the surgical procedures.